Force production and symmetry in water fitness exercises: a gender comparison - Catarina Santos; Mário Costa; Raul Bartolomeu; Tiago Barbosa; Luís Rama (Desafio Singular, 2021)
The aim of this study was to analyse and compare propulsive forces, relative force production and symmetry between genders during water fitness exercises. Eighteen participants (women, n=9; age: 20.67 ± 0.87 years; body mass: 58.18 ± 4.97 kg; height: 159.19 ± 5.85 cm; and men, n=9; age: 22.11 ± 1.76 years; body mass: 72.93 ± 7.00 kg; height: 170.83 ± 5.57 cm) underwent two incremental protocols performing horizontal adduction (HA) and the rocking horse (RHadd) exercises, from 105 to 150 bpm. Propulsive peak force of dominant (PFD) and non-dominant upper-limbs (PFND) was assessed by a differential pressure system. An isokinetic dynamometer was used to collect the dry-land isometric peak strength of the dominant upper-limb. Significant differences between genders were found for most of the music cadences in HA and RHadd. Men were able to produce higher propulsive force values for both upper-limbs during the overall incremental protocol, whereas women reached a higher relative force production. However, no significant differences were found between both genders at the same music cadence. Most actions were asymmetric in women, whereas men showed a symmetric pattern. The cadence of 135 bpm elicits a symmetric motion in both genders while exercising water fitness exercises. Keywords:aquatic exercise; propulsive force; isometric strength; cadence; sex